Corpus linguistics and linguistic theory: papers from the Twentieth International Conference on English Language Research on Computerized Corpora (ICAME 20) Freiburg im Breisgau 1999 - Mair, Christian; Hundt, Marianne (Language and computers, 2000)
From being the occupation of a marginal (and frequently marginalised) group of researchers, the linguistic analysis of machine-readable language corpora has moved to the mainstream of research on the English language. In this process an impressive body of results has accumulated which, over and above the intrinsic descriptive interest it holds for students of the English language, forces a major and systematic re-thinking of foundational issues in linguistic theory. Corpus linguistics and linguistic theory was accordingly chosen as the motto for the twentieth annual gathering of ICAME, the International Computer Archive of Modern/ Medieval English, which was hosted by the University of Freiburg (Germany) in 1999. The present volume, which presents selected papers from this conference, thus builds on previous successful work in the computer-aided description of English and at the same time represents an attempt at stock-taking and methodological reflection in a linguistic subdiscipline that has clearly come of age. Contributions cover all levels of linguistic description - from phonology/ prosody, through grammar and semantics to discourse-analytical issues such as genre or gender-specific linguistic usage. They are united by a desire to further the dialogue between the corpus-linguistic community and researchers working in other traditions. Thereby, the atmosphere ranges from undisguised skepticism (as expressed by Noam Chomsky in an interview which is part of the opening contribution by Bas Aarts) to empirically substantiated optimism (as, for example, in Bernadette Vine's significantly titled contribution Getting things done)
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Konferenzschrift -- 1999 -- Freiburg, Breisgau; Korpus; Englisch